A Correlation Study On Students’ Self Esteem And Speaking Ability Of 8th Grade At SMP IT Al Ibrah Gresik - Mohammad Tahmid; Khoirul Anwar; Ulfah Marifah (Jetlal, 2022)
Speaking is one of important way to communicate an ideas and message orally from the speaker to the receiver and the receiver can understand what the speaker talk about. Meanwhile, to reach degree of good speaker there is an aspect that need to give intention, that is self-esteem. Self-esteem becomes the important factor of human affective domain, that has been found to play an extremely important role while conducting communication activities. Here, the researcher has purpose to know whether there is significant correlation between students’ self-esteem and speaking ability or not. The respondents of this study were 84 randomly selected from 8th grade at SMP IT Al Ibrah Gresik. The students’ speaking ability depended on speaking score from English teacher and self-esteem taken from questionnaire consisting of 20 items. Meanwhile, to determine the correlation both of variables the researcher implemented Pearson Product Moment. The result showed that students’ speaking ability has proficient level (Mean = 80.327) and self-esteem at moderate level (Mean = 2.738). Finally, finding from the computation of data showed that there was positive and high correlation between self-esteem and speaking ability (r = 0.738) and also there was significant correlation with ρ = 0.00.